2017
DOI: 10.4236/ojbiphy.2017.73009
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tissue Regenerative Status on Hormesis in Dogs Irradiated during Their Lifespan

Abstract: The goal of this study was to evaluate the influence of natural variation in the regenerative status of dog tissues on the signs of hormesis, which are evident after total body exposure to low daily doses of external gamma radiation throughout the lifespan. Ninety beagle dogs of both sexes were irradiated with cobalt 60 at 0.003 Gy/day commencing 1 year after birth to death. Control (n = 169) and irradiated animals underwent whole-life clinical observation and autopsy, and were then retrospectively divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…There were no significant differences with controls in both exposed subgroups in terms of the incidence of solid malignancies, metaplasia, inflammation, diarrhea, and vomiting. These data confirmed the tendency of hormesis only in the weakest animals [155]. Because the frailty syndrome correlated with the loss of general somatic health and the loss of body weight [156], the data exclude the notion that radiation was associated with healing or stimulation and, Advances in Molecular Imaging instead, indicate that certain pathologies (e.g., hemoblastoses with high risk of quick death) may have only substituted for other nonfatal somatic problems in weaker animals [147] [154] [155].…”
Section: The Proof For An Indirect and "Competitive" Mechanismsupporting
confidence: 82%
See 1 more Smart Citation
“…There were no significant differences with controls in both exposed subgroups in terms of the incidence of solid malignancies, metaplasia, inflammation, diarrhea, and vomiting. These data confirmed the tendency of hormesis only in the weakest animals [155]. Because the frailty syndrome correlated with the loss of general somatic health and the loss of body weight [156], the data exclude the notion that radiation was associated with healing or stimulation and, Advances in Molecular Imaging instead, indicate that certain pathologies (e.g., hemoblastoses with high risk of quick death) may have only substituted for other nonfatal somatic problems in weaker animals [147] [154] [155].…”
Section: The Proof For An Indirect and "Competitive" Mechanismsupporting
confidence: 82%
“…These data confirmed the tendency of hormesis only in the weakest animals [155]. Because the frailty syndrome correlated with the loss of general somatic health and the loss of body weight [156], the data exclude the notion that radiation was associated with healing or stimulation and, Advances in Molecular Imaging instead, indicate that certain pathologies (e.g., hemoblastoses with high risk of quick death) may have only substituted for other nonfatal somatic problems in weaker animals [147] [154] [155]. It correlated with the typical "side effects" of conventional cytotoxic chemotherapy, which include body weight loss and immunosuppression, and was inseparable from the benefits afforded by any cyto- [159] were applicable to systemic treatments with any cytotoxic agents, without the need for any "stimulation" of immunity [160].…”
Section: The Proof For An Indirect and "Competitive" Mechanismsupporting
confidence: 82%
“…We did not find reasons for supporting the stimulation of anticancer immunity by any cytotoxic treatment, including long time metronomic therapy with low doses of anticancer drugs, as argued by Calabrese EJ and followers [70]. Analysis of the phenomenon of radiation hormesis showed that it does not disprove a linear hypothesis, being a result of redirection of morphogenic potency of the host from cancer tissue' growth to reparation/regeneration of the multitude of sub-lethal injures in non-malignant tissues of the body [71]. Giving low doses of cytotoxic chemotherapy may act that indirect way, simulating direct inactivation of cancer cells due to insufficiency of tumor endothelial net renewal [72].…”
Section: Resultsmentioning
confidence: 99%
“…Since 1998, we have been proving indirect mechanism of diminishing the cancer activity by slightly increased natural or artificial background radiation and low dose total/subtotal radiation therapy. In oppose to idea of radiogenic stimulation of anti-cancer immunity [8,9], the mechanism proposed by us bases on the redistribution of circulating morphogenic cells from tumor to exposed normal tissues [10][11][12][13], and was statistically tested [14,15]. As a proliferative resource of bone marrow is limited and associated very closely with the life span and the level of lymphopenia [16,17], the HBI with cumulative dose 9 Gy was employed mostly as myelosuppressive one.…”
Section: Discussionmentioning
confidence: 99%